Optimization of the development and location of agricultural clusters of regions (Texas Journal of Agriculture and Biological Sciences, 2022)
This article talks about the optimization of development, placement and economic efficiency of agro-industrial clusters of enterprises in the current conditions. The authors also share their thoughts on the issues of increasing the profits of agro-industrial clusters in the region.